2020
DOI: 10.23887/jpsu.v1i3.26852
|View full text |Cite
|
Sign up to set email alerts
|

Pendidikan Seks Untuk Anak Berkebutuhan Khusus Di Sma (Sekolah Menengah Atas) Luar Biasa C Negeri 2 Buleleng, Bali (Perspektif Sosiologi Pendidikan)

Abstract: Penelitian ini berawal dari perdebatan masyarakat mengenai pembelajaran pendidikan seks di sekolah. Namun di tengah perdebatan tersebut, justru pendidikan seks diajarkan di sekolah luar biasa C Negeri 2 Buleleng. Penelitian ini bertujuan untuk 1) Menambah pengetahuan peserta didik SMA Luar Biasa C Negeri 2 Buleleng mengenai pemahaman tentang pendidikan seks, sehingga dapat menerapkan dalam kehidupan sehari-hari. 2) Mengetahui pola interaksi guru dan peserta didik di dalam kelas maupun di luar kelas dalam konte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In a study conducted by Safitri (2020), dropout cases are caused by various factors, including (1) peer influence, (2) difficulty in following lessons, (3) low economic conditions of parents, and (4) lack of parental support. Furthermore, Wardani et al (2021) study also revealed several causes of children dropping out of school, including (1) low level of parental education, (2) low economic conditions combined with increasing family burdens, (3) lack of motivation for learning, (4) unsupportive environment, and (5) poor health.…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted by Safitri (2020), dropout cases are caused by various factors, including (1) peer influence, (2) difficulty in following lessons, (3) low economic conditions of parents, and (4) lack of parental support. Furthermore, Wardani et al (2021) study also revealed several causes of children dropping out of school, including (1) low level of parental education, (2) low economic conditions combined with increasing family burdens, (3) lack of motivation for learning, (4) unsupportive environment, and (5) poor health.…”
Section: Introductionmentioning
confidence: 99%